Pengaruh Beban Pajak Tangguhan Dan Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Ramdanu Nugroho; Dirvi Surya Abbas (Prosiding, 2022)
This study aims to obtain empirical evidence about the tax burden and tax planning on earnings management in the financial statements of companies listed on the Indonesia Stock Exchange (IDX). The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2015. The sample selection method used purposive sampling and obtained a sample of 32 companies. The data processing in this study uses panel data regression analysis using the Eviews 8 program. The results of this study show that deferred tax expense and tax planning have a positive effect on earnings management.